2018
DOI: 10.1128/jb.00249-18
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Viable but Nonculturable State and Antibiotic Persister Cells

Abstract: Bacteria have evolved numerous means of survival in adverse environments with dormancy, as represented by "persistence" and the "viable but nonculturable" (VBNC) state, now recognized to be common modes for such survival. VBNC cells have been defined as cells which, induced by some stress, become nonculturable on media that would normally support their growth but which can be demonstrated by various methods to be alive and capable of returning to a metabolically active and culturable state. Persister cells hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
176
3
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(207 citation statements)
references
References 116 publications
(151 reference statements)
7
176
3
5
Order By: Relevance
“…In the first case by the lack of staining of such cells with propidium iodide [78], in the second case by the possibility to resuscitate them in culture media [79]. It is suggested that a very thin sectioning during TEM preparation may contribute to the apparent lack of small, highly condensed nucleoid and protein aggregates, giving the effect of empty cytosol (ghost cells) ( Figure 6) [80]. Formation of these structures is promoted by the reduction in iATP and is crucial for the survival of microorganisms under stressogenic conditions [81].…”
Section: Morphostructure Determined By Tem In the Viability Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first case by the lack of staining of such cells with propidium iodide [78], in the second case by the possibility to resuscitate them in culture media [79]. It is suggested that a very thin sectioning during TEM preparation may contribute to the apparent lack of small, highly condensed nucleoid and protein aggregates, giving the effect of empty cytosol (ghost cells) ( Figure 6) [80]. Formation of these structures is promoted by the reduction in iATP and is crucial for the survival of microorganisms under stressogenic conditions [81].…”
Section: Morphostructure Determined By Tem In the Viability Assessmentmentioning
confidence: 99%
“…For this purpose, SYTO9/propidium iodide (so called Live/Dead) and NPN staining are most commonly used in H. pylori studies [69]. It seems that a basic criterion for cells with the VBNC phenotype, an integrity of cellular structures, contributes to an effective determination of the viability of coccoid H. pylori forms using the aforementioned methods [80]. It should be borne in mind, however, that morphological transition may somehow affect the adsorption or retention capacity of some fluorescent dyes.…”
Section: Fluorescence Determination In the Viability Assessmentmentioning
confidence: 99%
“…As virulence can be retained in the VBNC state, or regained upon resuscitation, it is essential to know whether a certain pathogen can persist in a VBNC state to develop reliable detection methods (Li et al ., ). Additionally, decontamination and treatment can be hindered, as dormant cells are often more resistant against antibiotics and harsh conditions in general (Oliver, ; Li et al ., ; Ayrapetyan et al ., ). In the case of A .…”
Section: Discussionmentioning
confidence: 97%
“…As virulence can be retained in the VBNC state, or regained upon resuscitation, it is essential to know whether a certain pathogen can persist in a VBNC state to develop reliable detection methods . Additionally, decontamination and treatment can be hindered, as dormant cells are often more resistant against antibiotics and harsh conditions in general (Oliver, 2010;Li et al, 2014;Ayrapetyan et al, 2018). In the case of A. baumannii, bacteria could undergo a switch to the VBNC state, for example in body fluids with elevated osmolarity, which would increase their persistence upon release to the hospital environment.…”
Section: Discussionmentioning
confidence: 99%
“…El estado VBNC describe una subpoblación de bacterias que han perdido transitoriamente su capacidad de crecer en los medios de cultivo de rutina en los que anteriormente podían crecer. Estas bacterias exhiben una actividad metabólica significativamente menor, aunque presente, que las bacterias en crecimiento activo, continúan manteniendo la integridad de su membrana y realizan la síntesis de proteínas (19) .…”
Section: Lm Viable Pero No Cultivable (Vbnc)unclassified